2014
DOI: 10.1186/1472-6963-14-208
|View full text |Cite
|
Sign up to set email alerts
|

Perceived competence and attitudes towards patients with suicidal behaviour: a survey of general practitioners, psychiatrists and internists

Abstract: BackgroundCompetence and attitudes to suicidal behaviour among physicians are important to provide high-quality care for a large patient group. The aim was to study different physicians’ attitudes towards suicidal behaviour and their perceived competence to care for suicidal patients.MethodsA random selection (n = 750) of all registered General Practitioners, Psychiatrists and Internists in Norway received a questionnaire. The response rate was 40%. The Understanding of Suicidal Patients Scale (USP; scores < 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 26 publications
2
53
0
4
Order By: Relevance
“…Practitioners generally reported positive attitudes toward individuals experiencing suicidality, with very few clinicians expressing endorsement of beliefs that could be characterized as stigmatizing (e.g., that suicidal individuals are weak). These findings are consistent with previous research that suggests stigma may not be a substantial factor in deciding to provide care (Grimholt, Haavet, Jacobsen, Sandvik, & Ekeberg, ).…”
Section: Discussionsupporting
confidence: 91%
“…Practitioners generally reported positive attitudes toward individuals experiencing suicidality, with very few clinicians expressing endorsement of beliefs that could be characterized as stigmatizing (e.g., that suicidal individuals are weak). These findings are consistent with previous research that suggests stigma may not be a substantial factor in deciding to provide care (Grimholt, Haavet, Jacobsen, Sandvik, & Ekeberg, ).…”
Section: Discussionsupporting
confidence: 91%
“…, Grimholt et al . ). However, no study has explored family caregivers' attitudes towards suicidal individuals.…”
Section: Discussionmentioning
confidence: 97%
“…This study demonstrated that the scores of family caregivers' SAS and SCAS were highly correlated. Studies have investigated various health professionals' attitudes towards suicide (Chan et al 2009, Grimholt et al 2014). However, no study has explored family caregivers' attitudes towards suicidal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…As atitudes dos profissionais de saúde diante de pessoas com comportamento suicida têm sido estudadas por diferentes pesquisadores em diversos países. Atitudes negativas e o modo como o profissional aborda o paciente podem influenciar a forma como a pessoa responderá ao cuidado oferecido [16][17][18]25,27,28 . No presente estudo, verificaram-se atitudes mais positivas em relação ao suicídio entre médicos e enfermeiros do que entre os agentes comunitários de saúde e técnicos de enfermagem, especificamente nos fatores "Sentimento" e "Capacidade Profissional" da escala utilizada.…”
Section: ▄ Discussãounclassified